Pseudorabies virus-induced expression and antiviral activity of type I or type III interferon depend on the type of infected epithelial cell - Yin, Yue; Ma, Jinglin; Van Waesberghe, Cliff; Devriendt, Bert; Favoreel, Herman W. (Frontiers in Immunology, 2022)
Type I and III Interferons (IFNs) are the initial antiviral cytokines produced in response to virus infection. These IFNs in turn bind to their respective receptors, trigger JAK-STAT signaling and induce the expression of IFN-stimulated genes (ISGs) to engage antiviral functions. Unlike the receptor for type I IFNs, which is expressed broadly on virtually every cell type, the expression of the type III IFN receptor is mainly restricted to epithelial cells that line mucosal surfaces. Accumulating evidence indicates that type III IFNs may play a unique role in protecting mucosal surfaces against viral challenges. PRV is a porcine alphaherpesvirus and causes huge economic losses to the pig industry worldwide. PRV first replicates in the respiratory tract, followed by spread via neurons and via lymph and blood vessels to the central nervous system and internal organs, e.g. the kidney, lungs and intestinal tract. In this study, we investigate whether PRV triggers the expression of type I and III IFNs and whether these IFNs exert antiviral activity against PRV in different porcine epithelial cells: porcine kidney epithelial cells (PK-15), primary respiratory epithelial cells (PoREC) and intestinal porcine epithelial cells (IPEC-J2). We show that PRV triggers a relatively slow but prominent type I and III IFN response in PK-15 cells, a rapid and temporal expression of both types of IFN in IPEC-J2 cells and virtually no expression of either IFN in PoREC. Pretreatment of the different cell types with equal amounts of porcine IFN-λ3 (type III IFN) or porcine IFN-α (type I IFN) showed that IFN-α, but not IFN-λ3, suppressed PRV replication and spread in PK-15 cells, whereas the opposite was observed in IPEC-J2 cells and both types of IFN showed anti-PRV activity in PoREC cells, although the antiviral activity of IFN-α was more potent than that of IFN-λ3 in the latter cell type. In conclusion, PRV-induced type I and III IFN responses and their antiviral activity depend to a large extent on the epithelial cell type used, and type III IFN display antiviral activity against PRV in epithelial cells from the respiratory and particularly the intestinal tract.